Board gender diversity and firm performance: A complexity theory perspective - Pandey, Nitesh; Kumar, Satish; Post, Corinne; Goodell, John W.; García-Ramos, Rebeca (Asia Pacific journal of management, 2023)
Over the years, researchers have used various theoretical frameworks and analytical tools to evaluate the relationship between board gender diversity and firm financial performance. The results, however, have remained largely inconclusive, perhaps because the role of board gender diversity has been studied separately from other board and firm characteristics. To address this issue, we examine the relationship between board gender diversity and firm financial performance through the theoretical framework of complexity theory, using qualitative comparative analysis (QCA). Our sample comprises 204 non-financial firms listed on the Bombay Stock Exchange (BSE). We find that board gender diversity does not affect firm financial performance in isolation, but rather in combination with other board and firm characteristics. In some combinations it is associated with both stronger firm financial performance and in other configurations with weaker firm financial performance. We also find that greater gender diversity on boards mitigates the negative effects of CEO duality on firm financial performance.